Adolescent family violence in Australia: A national study of prevalence, history of childhood victimisation and impacts - Fitz-Gibbon, Kate; Meyer, Silke; Boxall, Hayley; Maher, JaneMaree; Roberts, Steven (2022)
This report is organised into four key sections: Section 1 presents the prevalence study by drawing on the quantitative findings on violence used by young people in the home as well as the co-occurrence of experiencing family violence, being a direct target of family violence, and the perpetration of AFV. Section 2 presents the study findings specific to five priority adolescent cohorts: First Nations young people, young people from NESBs, young people with disability, gender-diverse young people, and young people with diverse sexual identities. Section 3 draws on the qualitative study components to examine young people’s rationale for using family violence in the home. Section 4 explores the impacts of adolescent family violence and experiences of family violence on young people in Australia. The findings from this stage of the research raise a number of implications for policy and practice. The findings highlight the critical need for greater trauma-informed practice when responding to families affected by DFV, including child abuse and AFV. Supporting a young person’s recovery from DFV is an essential strategy to reduce the risk of intergenerational violence, and other short- and long-term impacts of violence on children’s and young people’s lives.